AWARENESS OF GST AMONG RETAILERS IN CHENNAI DISTRICT - S. Santhiya Savithri; R., Samundeswari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Goods and Services Tax (GST) was implemented in India with the aim of simplifying the country's tax structure and fostering economic growth by unifying the indirect tax system. This study examines the association between the demographic profile and awareness of GST among retailers. Primary data were gathered from 100 retailers in Chennai District and they are analysed using statistical methods such as simple percentage analysis, chi-square test, z-test and ANOVA. The findings of the study reveal gaps in GST awareness and highlight the need for targeted training and support initiatives to bridge these gaps. By addressing these issues, the study provides actionable recommendations to enhance compliance and improve the overall effectiveness of GST implementation in the retail sector.